Humour as a pedagogical tool in teacher-initiated repair sequences: the case of extreme case formulations and candidate hearing. Issue 3 (3rd July 2021) - Çopur, Nimet; Atar, Cihat; Walsh, Steve
ABSTRACT: Research on humour in second language classrooms has widely focused on the roles, social functions and markers of humour in interaction; however, little attention has been paid to the sequential mechanisms of humour and the relationship between repair and humour. Therefore, drawing on a conversation analytic approach, this study investigates teacher-initiated humour as a repair initiator in naturally occurring interaction and the pedagogical outcomes created. Sixteen hours of data from English as a second language classroom contexts have been analysed using Conversation Analysis. Conversation Analysis provides valuable opportunities for humour studies with meticulous attention given to sequentiality, and its repair mechanism is a tool for understanding how interlocutors deal with troubles. The findings suggest that teachers accomplish various pedagogical goals by initiating repair on prior student turns in the form of confirmation checks, which they mark as humorous through extreme case formulations and candidate hearing produced in smiley voice. In doing so, they make students' turns disaffiliating and an elaboration relevant next, through which they elicit extended responses and create space for learning. Thus, via producing repair sequences as humorous, teachers progress their pedagogical agenda and also open up space for further language practice by encouraging elaboration and discussion.